OPTIMALISASI UMKM JAMU PUSPITASARI PUTRI BERBASIS TEKNOLOGI TEPAT GUNA DI DESA BEJI, KABUPATEN PEMALANG - Wisnu Broto; Edy Supriyo; Fahmi Arifan; Nanik Kartikasari; Alif Nur Fauzi Prasetyo; Susi Lestari; Tumiar Iriana (Sekolah Vokasi Universitas Diponegoro, 2023)
Beji is a village in Taman sub-district, Pemalang Regency, Central Java Province, Indonesia. Beji Village is approximately 1 km from the district capital or 4 km from the Pemalang Regency capital. Topographically, Beji Village is a lowland area which is the economic traffic of Pemalang Regency, so it is very suitable for agricultural and trading businesses. The trading commodities of Beji Village are the people's daily commodities such as food, drinks, clothing, medicines, and so on. With this regional position, Beji village has enormous economic potential from the agricultural and trade sectors. The potential in question is the presence of herbal drink production centers. In Beji Village, there is an UMKM Jamu Puspitasari Putri which is a producer of herbal drinks. MSMEs have difficulty in competing and running their business. Therefore, the community service program that will be implemented focuses on training innovations in the use of cup sealers and automatic expired date machines. In addition, the program was created with the aim that UMKM Jamu Puspitasari Putri can be more optimal in producing herbal drinks.